Case report: Rare oral manifestations in Cowden syndrome with PTEN mutation - Yuan, Wei; Liu, Yanbin; Sun, Haibin; Su, Ming; Qin, Lizheng; Huang, Xin (Frontiers in Oncology, 2024)
Background Cowden syndrome (CS) is a rare genetic disorder associated with PTEN gene mutations. It is characterized by macrocephaly, specific mucocutaneous features, and a predisposition to benign and malignant tumors. Cases of CS primarily presenting with oral clinical manifestations are relatively uncommon. Methods/Results We report the case of a 41-year-old male proband who presented with bilateral commissural and lingual externally projecting symmetric lesions for over two years. The proband also exhibited other features, including macrocephaly, communication difficulties, and obesity. Similar oral clinical manifestations were observed in family members. Whole exome sequencing analysis revealed PTEN gene mutations associated with CS in both the proband and his younger brother. This case serves as a reminder to be aware of the diverse presentations of CS in oral clinical practice and highlights the importance of genetic testing for guiding diagnosis and treatment. Conclusion There are few reported cases of CS primarily presenting with oral lesions. This finding contributes to further understanding of certain aspects of the pathogenesis of CS and enhances awareness of CS cases primarily exhibiting oral clinical manifestations.